Medherbs: games in learning medicinal herbs / Nor Erna Amira Amran - Amran, Nor Erna Amira (2012)
There are many advantages of medicinal herbs. Although it has many advantages, but majority of the teenagers do not know about the medicinal herbs and how its look likes. The objectives of this project are to design a learning game which introduce a few medicinal herbs and its uses, to design a learning game which introduce a few medicinal herbs and its uses and to develop the learning game which introduce a few medicinal herbs to test the functionality of the games. The MedHerbs game have been designed and developed as a learning tool to learn about the medicinal herbs. The MedHerbs have provided an attractive graphical user interface, so that the user will not easily get bored by playing the games. This project will benefit to the teenagers who want to learn about medicinal herbs. They can have a fun way to learn about the medicinal herbs and its uses. Adobe Flash CS5.5 and actionscript 3 have been used to develop this project prototype. As a conclusion, teenagers will easily learn about the medicinal herbs and its uses by playing the MedHerbs games.